Pengaruh Kualitas Produk, Kualitas Pelayanan,Harga, Promosi Dan Lokasi Terhadap Keputusan Pembelian Pada Mixue Di Jember - Nuril Auwalin; Nely Supeni; Hayatul Maspufah (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study was conducted to determine the influence of Product Quality, Service Quality, Price, Promotion, and Location on Purchase Decision at Mixue Patrang Jember. The research data were obtained through the distribution of questionnaires to respondents who had made purchases at Mixue. The sampling method used was non-probability sampling with a purposive sampling technique. The population in this study consisted of consumers of Mixue Patrang Jember, with a total sample of 60 respondents. The data analysis techniques used included Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Coefficient of Determination Test, t-test, and F-test, as well as multiple linear regression analysis with the help of SPSS Version 25. The results of the study show that partially, the variables Product Quality and Price have a significant influence on purchase decisions, while Service Quality, Promotion, and Location do not have a significant effect. However, simultaneously, all five variables significantly influence purchase decisions at Mixue Patrang Jember.